Novel diagnostics for improved treatment of gynecological cancer - Ulf Gyllensten (Upsala Journal of Medical Sciences)
This paper summarizes the efforts to develop novel biomarkers for diagnosis and screening of the three main gynecological cancers, cervical, endometrial, and ovarian cancer, with an emphasis on research performed during the last 20 years in Uppsala. A cervical cancer screening program has existed in Sweden since 1966 using cytology as the primary test. Over the last two decades, research has provided the scientific base for a transition to self-sampling to improve convenience of the woman and achieve higher population coverage, and use of human papillomavirus as the primary test. Also, efficient prophylactic vaccines and more efficient treatment strategies of women with cervical dysplasia have been introduced. Together, these medical tools have the potential to eradicate cervical cancer by 2120, as envisaged by WHO. By contrast, efficient biomarkers for endometrial and ovarian cancer are still lacking. Through the use of high-throughput proteomics, we have identified novel plasma protein biomarkers to be used in the diagnosis of women with adnexal ovarian mass upon transvaginal ultrasound, and possibly also for early detection in population screening. Similarly, novel biomarkers for the diagnosis of endometrial cancer are being evaluated. To establish a population-based screening program requires careful cost-benefit analyses. One alternative would be to broaden the focus of the current cervical cancer screening program to include also the novel biomarkers for ovarian and endometrial cancer, and thereby achieve screening for all three gynecological cancers. A program that screens for all three diseases could increase motivation to participate and thereby population coverage.